Chitosan Enhances the Anti-Biofilm Activity of Biodentine against an Interkingdom Biofilm Model - Sumaya Abusrewil; Jason L. Brown; Christopher Delaney; Mark C. Butcher; Mohammed Tiba; J. Alun Scott; Gordon Ramage; William McLean (MDPI AG, 2021)
Endodontic infection is a biofilm disease that is difficult to irradicate with current treatment protocols, and as such, persistent micro-organisms may lead to ongoing or recurrent disease. The potential for the use of enhanced filling materials to modify biofilm regrowth is a promising strategy. This current study aimed to evaluate the anti-biofilm efficacy of calcium silicate cements modified with chitosan. The development of mono-species and multi-species biofilms on ProRoot MTA, Biodentine and bovine dentine discs were explored using quantitative microbiology analysis. The effect on regrowth of biofilms was assessed following the addition of chitosan to each cement. In comparison to a dentine substrate, both materials did not show the ability to inhibit biofilm regrowth. Biodentine incorporated with chitosan displayed a dose-dependent reduction in multi-species biofilm regrowth, unlike MTA. Notably, interkingdom biofilms were shown to enhance bacterial tolerance in the presence of chitosan. This study demonstrates the potential to enhance the antimicrobial properties of Biodentine. The findings highlight the need for appropriate model systems when exploring antimicrobial properties of materials in vitro so that interspecies and interkingdom interactions that modify tolerance are not overlooked while still supporting the development of innovative materials.